Struggle and Strategies Faced by Vocational High School During the COVID-19 - Rahmatika Kayyis; Dita Ayuningtyas; Fatma Yuniarti (ENLIT, 2022)
This research aims to describe, explain and analyze the struggles and strategies faced by Vocational High School during the Covid-19 in Vocational High School Pringsewu. The subject in this study was an English teacher of Vocational High School Pringsewu. The research method used is descriptive qualitative. Observation, interviews, and questionnaires were used for collecting data. The results of this study indicate that teachers applied online teaching techniques to meet the requirement of teaching English in both practice and theory based on the syllabus. During the implementation, teachers experienced limited ability in explaining material to students, not all students understood the material presented by the teacher. The teacher did not know the students' abilities and characters. The strategies used by teachers in online learning have not been maximal and effective.